Numerical Simulation of Film Cooling Over Flat Plate - Ennil, Ali S. Bahr; Elfaghi, Abdulhafid M. (New Approaches in Engineering Research Vol. 12, 2021)
The commercial CFD Ansys Fluent program is used to explore the effect of film cooling across a flat plate. The coolant supply tube and the primary mixing zone are included in the computational domain. For blowing ratios of 0.33, 0.5, and 1.67, and a density ratio of 1.14, a tube L/D of 4 and injection angles of (30o, 60o, and 90o) were used. Adiabatic film cooling effectiveness distributions for inline and staggered configurations were also established. The primary finding of this study was that the 30o hole had higher efficacy values than the 60o and 90o holes when the blowing ratio was 0.33 and the length-to-diameter ratio was the same. A blowing ratio of 0.5 was found to be the most effective. The results reveal that increasing the blowing ratio has a negative impact on film cooling, with the injected coolant tending to lift off the wall at a blowing ratio of 1.67 due to an increase in the wall normal momentum. The numerical results are compared to experimental data in this section.